PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN STRUKTUR GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI - Niyanti Anggitasari; Siti Mutmainah (Diponegoro Journal of Accounting, 2012)
This research is to investigate the influence of corporate social responsibility disclosure and good corporate governance structures to relationship between financial performance and firm value. . The aim of this research is to find empirical proof about (a) the influence of financial performance to firm value, (b) the influence of independent commissioners as moderating variable in the relationships between financial performance and firm value, (c) the influence of institutions ownership as moderating variable in relationships between financial performance and firm value, (d) the influence of managerial ownership as moderating variable in relationships between financial performance and firm value,(e) the influence of audit committee as moderating variable in relationships between financial performance and firm value,(f) the influence of disclosure CSR as moderating variable in relationships between financial performance and firm value. ROA is used as the proxy of financial performance and Tobins Q is used as the proxy of firm value. The sample of this research is manufacture firms which is listed on Indonesia Stock Exchange (IDX) over 2007-2010. The research sample are 24 firms with 96 observations. The analysis methods of this research use simple regression analysis for hypothesis 1 and multiple regression analysis with the Moderated Regression Analysis (MRA) for hypothesis 2 until 6. The results of this research show that ROA doesn’t have significant influence to Tobins Q, meanwhile the analysis with the moderating variable MRA shows that independent commissioners, managerial ownership and audit committee can’t moderate in relation between ROA and Tobins Q. Institutions ownership and CSR disclosure moderate in relation between ROA and Tobins Q that it shows positive significant influenence.